(untitled) (Research, Society and Development, 2020)
The conversion of the native Cerrado into agricultural systems promotes a reduction in the input of organic residues on the soil, which can compromise the contents of soil organic carbon. The spatial distribution of carbon and nitrogen stocks in the soil is normally influenced by environmental and anthropogenic factors. This research aimed to map and evaluate the spatial variability of carbon and nitrogen stocks in the soil, in different integrated systems and pasture areas in the edaphoclimatic conditions of the Cerrado biome, in the state of Maranhão. The work was set up in a Red-Yellow Latosol with different management methods: crop-livestock integration with no-till farming, crop-livestock integration with patch scarification and harrowing, crop-livestock-forest integration, and pasture. The samples were removed at a depth of 0.0-0.20 m, in a grid with a regular interval of 50 m, totaling 193 points. The data were subjected to descriptive statistics, geostatistics, and kriging interpolation. The mean and median values are similar for the carbon and nitrogen stocks, in their respective management systems, indicating symmetric data distribution, confirmed by the asymmetry and kurtosis values close to zero. The spatial distribution of the carbon stocks is more homogeneous in the crop-livestock integration with no-till farming, whereas the crop-livestock integration with patch scarification and harrowing presents greater homogeneity in nitrogen distribution.